2014
DOI: 10.1139/apnm-2013-0365
|View full text |Cite
|
Sign up to set email alerts
|

Lifelong exposure to n-3 PUFA affects pubertal mammary gland development

Abstract: There is growing evidence that early developmental periods may importantly influence future breast cancer risk. Also, there is great interest in the role of dietary fat in breast cancer risk, but the role of dietary fat during pubertal mammary gland development remains poorly understood. This study investigated the effect of n-3 polyunsaturated fatty acids (PUFA) using complementary dietary and genetic approaches to examine the effect of lifelong exposure of n-3 PUFA or n-6 PUFA (control) on mammary gland deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 33 publications
3
25
0
Order By: Relevance
“…Many mechanisms have been proposed to account for the effects of n-3 PUFAs on cancer [ 8 ]. These include changes in toxicity to stem cells [ 20 ], metabolic programing and morphological development of the mammary gland [ 21 ], cell proliferation [ 22 , 23 ], production of inflammation-inducible cytokines and eicosanoids [ 24 ], PPAR activation [ 25 , 26 ], fatty acid synthesis and metabolism [ 27 , 28 ], angiogenesis [ 29 , 30 ], and lipid peroxidation [ 31 ] to list but a few.…”
Section: Discussionmentioning
confidence: 99%
“…Many mechanisms have been proposed to account for the effects of n-3 PUFAs on cancer [ 8 ]. These include changes in toxicity to stem cells [ 20 ], metabolic programing and morphological development of the mammary gland [ 21 ], cell proliferation [ 22 , 23 ], production of inflammation-inducible cytokines and eicosanoids [ 24 ], PPAR activation [ 25 , 26 ], fatty acid synthesis and metabolism [ 27 , 28 ], angiogenesis [ 29 , 30 ], and lipid peroxidation [ 31 ] to list but a few.…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate attention has been paid to the various ways in which SES may contribute to breast cancer risk over the lifecourse, but especially in the early childhood period, via the many pathways that are associated with specific risk factors. The association of low SES with early menarche, which is also associated with an increased risk of breast cancer, is one example. Over the last 50 years, the average age of menarche has declined in the United States for both black and white women, but there has consistently been an almost 2‐fold greater risk of early menarche for black females versus white females .…”
Section: Lifecourse Approach: the Link Between Cumulative Adversity Amentioning
confidence: 99%
“…In addition, our recent findings showed that lauric acid, a medium-chain fatty acid (MCFA), stimulated mammary gland development in pubertal mice [ 9 ]. Furthermore, long-chain fatty acids (LCFA) such as n-3 and n-6 polyunsaturated fatty acids (PUFA), have been reported to play important roles in the morphological development of the mammary gland during puberty [ 10 ]. However, the effects of monounsaturated LCFA on the development of pubertal mammary glands are rarely studied.…”
Section: Introductionmentioning
confidence: 99%